2021
DOI: 10.1038/s41523-021-00311-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1b clinical trial of ado-trastuzumab emtansine and ribociclib for HER2-positive metastatic breast cancer

Abstract: Patients with HER2+ metastatic breast cancer are often treated with a multitude of therapies in the metastatic setting, and additional strategies to prolong responses to anti-HER2 therapies are needed. Preclinical evidence suggests synergy between cyclin-dependent kinase 4 and 6 (CDK 4/6) inhibitors and anti-HER2 therapies. We conducted a phase 1b study of ribociclib and ado-trastuzumab emtansine (T-DM1) in patients with advanced/metastatic HER2-positive breast cancer previously treated with trastuzumab and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Most recently, the data of a phase 1b trial in a very small cohort ( N = 12) show promising clinical activity of ribociclib in combination with T-DM1 in HER2+ MBC patients regardless of their HR status (66.7% of patients had HR+/HER2+) [ 110 ]. While CDKi can impair the efficacy of T-DM1 by preventing cells from entering into the S or M phase [ 111 ], it can potentially be avoided with a non-overlapping dosing strategy [ 110 ]. This scheme can also mitigate toxicities common with both agents, e.g., thrombocytopenia.…”
Section: Towards a Common Goal Of A Chemotherapy-sparing Treatment Planmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, the data of a phase 1b trial in a very small cohort ( N = 12) show promising clinical activity of ribociclib in combination with T-DM1 in HER2+ MBC patients regardless of their HR status (66.7% of patients had HR+/HER2+) [ 110 ]. While CDKi can impair the efficacy of T-DM1 by preventing cells from entering into the S or M phase [ 111 ], it can potentially be avoided with a non-overlapping dosing strategy [ 110 ]. This scheme can also mitigate toxicities common with both agents, e.g., thrombocytopenia.…”
Section: Towards a Common Goal Of A Chemotherapy-sparing Treatment Planmentioning
confidence: 99%
“…T-DM1 was administered intravenously on day 1 of each 21-day cycle, followed by ribociclib on days 8–21 of a 21-day cycle. After a median follow-up of 12.4 months, the median PFS was 10.4 months, and the combination was generally well-tolerated, with the majority of toxicities reported in grades 1 and 2 [ 110 ].…”
Section: Towards a Common Goal Of A Chemotherapy-sparing Treatment Planmentioning
confidence: 99%
“…No dose-limiting toxicities were observed, and the majority of adverse events were graded as 1 or 2, with only grade 3 neutropenia, leukopenia, and anemia, usually reported with CDK4/6 monotherapy. 19 …”
Section: Emerging Combinations In Metastatic Settingmentioning
confidence: 99%
“…42 A phase 1b study combined ribociclib and T-DM1 in patients with HER2+ MBC previously treated with trastuzumab and a taxane. 43 Based on the pharmacokinetic analysis, AEs, and dose reductions, 400 mg was determined to be the recommended phase II dose (RP2D) for ribociclib given with T-DM1.…”
Section: Combination Of T-dm1 and Cdk4/6 Inhibitorsmentioning
confidence: 99%
“…Cardiotoxicity was an unusual finding among patients treated with T-DM1 after anthracycline-based chemotherapy. 43,44 Verma et al 8 reported that 97% of patients receiving T-DM1 maintained an LVEF of ≥ 45%. This is consistent with the results of other landmark studies reporting that very few patients discontinue treatment due to cardiotoxicity.…”
Section: Cardiovascular Toxicitiesmentioning
confidence: 99%